Formation of SiO2@C–Ni magnetic nanotubes with excellent performance in 4-nitrophenol reduction. Issue 47 (21st November 2022) - Jin, Yuqin; Zheng, Jing; Zhu, Linyu; Yin, Xue-Bo; Zhang, Min
Abstract : Herein, a facile and controllable strategy was proposed for the fabrication of SiO2 @C–Ni nanotubes, and the resulting composite exhibited outstanding catalytic performance towards the reduction of 4-nitrophenol (4-NP). Abstract : A facile and rational strategy for immobilizing nickel nanoparticles (Ni NPs) on silica nanotubes (SiO2 @C–Ni) was developed via the Stöber method, nickel ion mediated dopamine polymerization and carbonization treatment, coupled with removal of the template of one-dimensional (1D) MnO2 nanowires (NWs). The as-prepared SiO2 @C–Ni nanotubes show vast interior space with a large specific surface area and an open channel, which offer a spacious transport channel for molecular diffusion and electron transfer. Consequently, SiO2 @C–Ni nanotubes exhibited outstanding catalytic efficiency and excellent stability for 4-nitrophenol (4-NP) reduction. Their superior catalytic activity could be ascribed to the high coverage of Ni NPs and the tubular structure of the obtained SiO2 @C–Ni, by which the silica nanotubes enhanced the accessibility of the active sites and increased the mass transfer. This facile and controllable strategy may introduce a new avenue for designing metal NP-supported composites with high dispersion for diverse applications.